1998
DOI: 10.1104/pp.116.2.627
|View full text |Cite
|
Sign up to set email alerts
|

Stress Induction of Mitochondrial Formate Dehydrogenase in Potato Leaves1

Abstract: In higher plants formate dehydrogenase (FDH, EC 1.2.1.2.) is a mitochondrial, NAD-dependent enzyme. We previously reported that in potato (Solanum tuberosum L.) FDH expression is high in tubers but low in green leaves. Here we show that in isolated tuber mitochondria FDH is involved in formate-dependent O 2 uptake coupled to ATP synthesis. The effects of various environmental and chemical factors on FDH expression in leaves were tested using the mitochondrial serine hydroxymethyltransferase as a control. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(94 citation statements)
references
References 28 publications
4
90
0
Order By: Relevance
“…In barley roots, the expression of FDH is induced by iron deficiency, an induction that appears to be a secondary effect of the oxygen deficiency resulting from iron deficiency (Suzuki et al, 1998). It has also been proposed that glycolysis may play an important role in the FDH expression in response to abiotic stresses (Hourton-Cabassa et al, 1998). Similarly, we have previously shown that genes involved in glycolysis are repressed, but that genes related to anaerobic respiration are promoted by Al stress in rice bean root apices , implying that hypoxia and glycolysis may be responsible for rice bean VuFDH expression in response to Al stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In barley roots, the expression of FDH is induced by iron deficiency, an induction that appears to be a secondary effect of the oxygen deficiency resulting from iron deficiency (Suzuki et al, 1998). It has also been proposed that glycolysis may play an important role in the FDH expression in response to abiotic stresses (Hourton-Cabassa et al, 1998). Similarly, we have previously shown that genes involved in glycolysis are repressed, but that genes related to anaerobic respiration are promoted by Al stress in rice bean root apices , implying that hypoxia and glycolysis may be responsible for rice bean VuFDH expression in response to Al stress.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, FDHs have been reported to be involved in stress responses, because the expression of FDHs was responsive to a wide range of abiotic and biotic stresses (Hourton-Cabassa et al, 1998;David et al, 2010). Recently, Choi et al (2014) reported that FDHs play important role in hypersensitive response-like cell death and defense responses to bacterial pathogens in both peppers (Capsicum annuum) and Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…A proposed mechanism for the involvement of At4g17360 and At5g47435 as putative folate deformylases in photorespiration is shown in Figure 10. A similar, but not a cyclic, route involving folate interconversion enzymes has previously been postulated to produce formate in plants (Hourton-Cabassa et al, 1998;Hanson et al, 2000;Goyer et al, 2005). (Photorespiration involves a series of cycles to metabolize toxic 2-phosphoglycolate and to prevent both the depletion of intermediates and cofactors and the accumulation of products due to large fluxes.)…”
Section: Functions Of At4g17360 and At5g47435 Proteins In Photorespirmentioning
confidence: 99%
“…In addition, the resulting formate can also be decarboxylated in the peroxisomes by its oxidation via catalase and H 2 O 2 (Halliwel and Butt, 1974) or can be oxidized to CO 2 by formate dehydrogenase in the mitochondrion (Hourton-Cabassa et al, 1998). These potential reactions are shown in Figure 5.…”
Section: Photorespiratory Metabolitesmentioning
confidence: 99%